Plasma concentrations of ascorbic acid in a cross section of the German population - Hagel, Alexander; Albrecht, Heinz; Dauth, Wolfgang; Hagel, Wolfgang; Vitali, Francesco; Ganzleben, Ingo; Schultis, Hans W.; Konturek, Peter C.; Stein, Juergen; Neurath, Markus; Raithel, Martin (Journal of International Medical Research, 2018)
Objectives Vitamin C deficiency is considered extremely rare in modern industrialized countries. This study was performed to assess vitamin C concentrations in the German population. Methods As part of a consultant-patient seminar on nutrition and food intolerances, patients were asked to participate in this study on a voluntary basis. Blood samples were taken for analysis of serum vitamin C concentrations, and all patients were asked to complete a questionnaire. The vitamin C concentration was determined by high-performance liquid chromatography. Results Of approximately 300 patients attending the seminar, 188 (62.6%) consented to vitamin C blood sample analysis and 178 (59.3%) answered the questionnaire. The mean vitamin C concentration was 7.98 mg/L (range, 0.50-17.40; reference range, 5-15 mg/L). A low plasma level with vitamin C insufficiency (<5 mg/L) was found in 31 patients (17.4%), and a potential scorbutogenic deficiency (<1.5 mg/L) was found in 6 (3.3%). Conclusions Potential vitamin C insufficiency and deficiency is common. It is therefore possible, even in modern developed populations, that certain individuals may require a higher intake of vitamin C.
EVALuna2:33798